Mathematical modeling of the Kalankuttiya branch canal application of software "Mistral/Simutra" - Sally, Hilmy (International Irrigation Management Institute, 1987)
The International Water Management Institute contracted with the French consulting firm, SOGREAH, to furnish us with their Micro-computer software package for flow simulation in canals, "MISTRAL/ SIMUTRA". The objective of this paper is to describe the software, its data requirements, output, and potential use through a discussion of its application to the Kalankuttiya branch canal in the Mahaweli System H in the North-Central Province of Sri Lanka.